Respuesta :

Answer:

a) [tex]P(B/A) = P(B)[/tex]

Step-by-step explanation:

Step(i):-

Given that A and B are independent events

P(A∩B) =P(A) P(B)

we will use the conditional probability

              [tex]P(A/B) = \frac{P(AnB)}{P(B)}[/tex]

                     or

            [tex]P(B/A) = \frac{P(AnB)}{P(A)}[/tex]

Step(ii):-

Given that A and B are independent events

P(A∩B) =P(A) P(B)

 [tex]P(B/A) = \frac{P(AnB)}{P(A)}[/tex]

[tex]P(B/A) = \frac{P(A)P(B)}{P(A)} = P(B)[/tex]

[tex]P(B/A) = P(B)[/tex]

ACCESS MORE